Space requirement of finishing pigs fed to heavier weight - David A Nichols; Robert H Hines; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1988)
Two trials, using a total of 240, crossbred, finishing pigs were conducted to evaluate 7, 9, and 11 ft^2 space allowance per pig from approximately 115 lb to a market weight of 250 lb. Pigs were removed individually each week as they reached the desired weight. Pigs reared in pens with 7 ft^2 had a reduced average daily feed intake and a significantly reduced average daily gain compared to those with 9 and 11 ft^2. Feed/gain was the same for all treatments; however, the pigs with 7 ft^2 required 4 days longer to reach 250 lb. Performance data suggests that 7 ft^2 is inadequate space allowance for pigs carried to heavier weights. No significant differences were observed in average daily gain, feed intake, or feed efficiency for pigs with 9 or 11 ft^2 allowance, suggesting that 9 ft^2 per pig is adequate space for this management system of removing pigs weekly as they reached the desired market weight.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Space requirement; Finishing pigs; Heavy weight